Education and content of civil defence training in Czechoslovakia in the years between 1938 and 1951 - Kavan, Štěpán; Kováčová, Lucie (STEF92 Technology Ltd., 2018)
This article is a reflection of civil defence education as one of basic element of education. The research focuses on the period 1938 – 1951; period between the time before World War II burst out and the time of political changes in the Czechoslovakia. The aim of the research is to explore the basic approaches to the implementation of education in relation to civil defence education in Czechoslovakia. The comparative historical analysis is utilized as the research method on the subject of civil defence education. The comparative historical analysis is used as a specific tool for qualitative research. This is a procedure which can be applied to the statehood issue of education to its basic elements, by which it will be possible to learn more about this phenomenon and subsequently explain it. Perceptions and ideas about the tasks of the state have gradually changed and evolved. This means the creation and development of the legal order, providing security and order within the state. Civil defence education was directed to such education and creating an environment so that every citizen, irrespective of nationality, religion, political opinion and social environment in which they live, has the physical and mental ability and willing to enthusiastically and faithfully fulfill their civic duties.
Vzdělávání a obsah branné výchovy v Československu v období let 1938 - 1951
Keywords: civil defence; education; security; state; statehood; branná výchova, vzdělávání, bezpečnost, stát, vlastenectví